2018
DOI: 10.1037/apl0000299
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of agency: Feeling powerful reduces brokerage opportunity recognition yet increases willingness to broker.

Abstract: Research suggests positions of brokerage in organizational networks provide many benefits, but studies tend to assume everyone is equally able to perceive and willing to act on brokerage opportunities. Here we challenge these assumptions in a direct investigation of whether people can perceive brokerage opportunities and are willing to broker. We propose that the psychological experience of power diminishes individuals' ability to perceive opportunities to broker between people who are not directly connected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 80 publications
(126 reference statements)
1
20
0
1
Order By: Relevance
“…Although conceptualizations of brokerage and brokering vary, researchers commonly agree that network structure sets the stage for brokering activity (Landis, Kilduff, Menges, & Kilduff, 2018;Obstfeld, FIGURE 1 An Integrative View of Brokering as Intermediation and/or Modification 2017). Our review of the research on brokerage and brokering identified the need for greater integration between social structure and social process as a key theme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although conceptualizations of brokerage and brokering vary, researchers commonly agree that network structure sets the stage for brokering activity (Landis, Kilduff, Menges, & Kilduff, 2018;Obstfeld, FIGURE 1 An Integrative View of Brokering as Intermediation and/or Modification 2017). Our review of the research on brokerage and brokering identified the need for greater integration between social structure and social process as a key theme.…”
Section: Discussionmentioning
confidence: 99%
“…The research we reviewed, however, suggests that personality traits, such as self-monitoring, play an important role in shaping brokering processes in organizations (Kilduff & Brass, 2010;Kilduff & Day, 1994;Mehra, Kilduff, & Brass, 2001;Oh & Kilduff, 2008;Sasovova, Mehra, Borgatti, & Schippers, 2010). Related research has considered how individual differences in sense of power (Landis et al, 2018), traits such as openness to experience (Baer, 2010), and the ability and motivation to share information (Reinholt, Pedersen, & Foss, 2011) influence brokering processes and outcomes. Recent research has also considered interactions between different individual characteristics, documenting, for example, that self-reported differences in self-monitoring interact with perceived empathy (as reported by peers) in shaping changes in MBA students' networks (Kleinbaum, Jordan, & Audia, 2015).…”
Section: Situational Versus Personal Antecedents Of Brokering Processesmentioning
confidence: 99%
“…High-status brokers attract disconnected alters because the brokers are prominent in the overall network and have selection power over whom to associate with (Sauder, Lynn, & Podolny, 2012). Moreover, feeling powerful increases one’s willingness to broker, though it reduces brokerage opportunity recognition at the same time (Landis, Kilduff, Menges, & Kilduff, 2018). However, at the organizational level, Chandler, Haunschild, Rhee, and Beckman (2013) found a negative link between status and brokerage for firms.…”
Section: A Framework For Understanding Network Brokeragementioning
confidence: 99%
“…Hansen, ). Our approach to conceptualizing and measuring KS networks is also in line with prior research (e.g., Landis, Kilduff, Menges, & Kilduff, ; Podolny & Baron, ).…”
Section: Methodsmentioning
confidence: 62%